Processing and Properties of MDF Fibre-Reinforced Biopolyesters with Chain Extender Additives - Armin Thumm; Damien Even; Pierre-Yves Gini; Mathias Sorieul (International Journal of Polymer Science)
Biopolyesters are a way to improve natural fibre composite sustainability. This study explores, for the first time, the potential of using medium density fibreboard (MDF) fibres to reinforce four biobased and biodegradable polyester matrices to create a fully “green composite.” Added at 30 wt %, MDF fibres did not improve the strength of the injection moulded NFCs and this deficiency was investigated by measuring fibre length, viscosity, and molecular weight of the matrices. Compared to other lignocellulosic fibres, the use of MDF fibres led to a molecular weight reduction of biopolyesters during processing. This effect was particularly striking for PLA. The addition of a chain extender enhanced the molecular weight of PLA and improved its processability. The tensile strength increase was correlated to a reduction of fibre pull-out, enabling the MDF fibre to fulfil its expected reinforcement role within the biopolyester composite.